(untitled) (Journal of Universal Excellence, 2026)
Research Question (RQ): What is the attitude of students and graduates of business and economics towards learning foreign languages? Are there differences between employed and unemployed and between undergraduate and postgraduate students? Purpose: The purpose of this paper is to help planners of educational programs in the field of economics and business by analysing the attitude of students and graduates in this professional field towards learning foreign languages. Method: Descriptive method was used in the theoretical part, data were collected using the online tool 1ka, and then processed with the SPSS program, using descriptive statistical analysis, which allowed showing the distribution of respondents. Finally, factor and correlation analyses were used in order to test the relations between variables. Results: The results obtained on a sample of 283 respondents show that the studied population often faces the need for knowledge of foreign languages. Employees, especially those in jobs where higher education is needed, are more aware of this need. Likewise, the perception of the need for foreign language skills increases with the level of study, and knowledge of English alone does not meet all the needs. Organization: The study presents the attitude towards foreign languages by segments; it divides the population into undergraduate and postgraduate students and graduates without status, then examines the relationship according to activity in the labour market (divides the population into inactive, employed through student services and regularly or. self-employed). Society: The results of the study offer an insight into the current situation in the segment of Slovenian society which operates in the field of economics and business; emphasizes the importance of learning foreign languages in this professional field and sets the starting point for modifying the role of languages in business and economic study programs. Originality: One of the first comprehensive studies on the attitude of Slovenian students of economics and business towards learning foreign languages in the last decade. Limitations / further research: Further research is recommended among the student population over a longer period of time, in different environments and in different professional fields.